Policing youth : Britain, 1945-70 - Jackson, Louise A. (Louise Ainsley), 1967-; Bartie, Angela (Book collections on Project MUSE., 2014)
'Policing Youth' probes beneath the media sensationalism surrounding youth crime in order to evaluate the workings of juvenile justice and the relationship between young people and practitioners in a key era of social change (1945-70). The work of state representatives - the police, magistrates and probation officers - is mapped alongside models of discipline within families, neighbourhoods, schools and churches as well as the growing commercial sector of retail and leisure. Youth culture is considered alongside the social and moral regulation of everyday life.